Evaluation of the yeast phase-specific monoclonal antibody 4D1 and Galanthus nivalis agglutinin sandwich ELISA to detect Talaromyces marneffei antigen in human urine - Shu, Fangyi; Pruksaphon, Kritsada; Nosanchuk, Joshua D.; Thammasit, Patcharin; Youngchim, Sirida (Frontiers in Cellular and Infection Microbiology, 2023)
Talaromyces (Penicillium) marneffei (TM) is an important, but neglected, thermally dimorphic fungus. It is the pathogenic cause of talaromycosis, which is strongly associated with the immunodeficiency state present in individuals with advanced HIV disease. The purpose of this study was to develop a sandwich enzyme-linked immunosorbent assay (sandwich ELISA) for the detection of T. marneffei cytoplasmic yeast antigen (TM CYA) in human urine. Monoclonal antibody (MAb) 4D1 specifically binds to TM CYA. Galanthus nivalis agglutinin (GNA), a mannose -binding lectin, recognizes and binds to mannose residues of TM CYA. For the sandwich ELISA, the microplate was coated with GNA as the capturing molecule for absorbing immune complexes of MAb 4D1-TM CYA. The MAb 4D1-GNA sandwich ELISA did not detect a cross-reaction with other antigens from other fungi or bacteria. Seventy-four urine samples from patients with blood culture -confirmed talaromycosis and 229 urine samples from people without talaromycosis residing in the endemic area were subjected to the MAb 4D1-GNA sandwich ELISA. At an optical density (OD) cutoff value of 0.356, the sensitivity was 89.19% [95% confidence interval (CI): 79.80% –95.22%]; the specificity was 98.69% (95% CI: 96.22% –99.73%). The diagnostic performance of the MAb 4D1-GNA sandwich ELISA was highly consistent with those of blood culture and the Platelia Aspergillus galactomannan (GM) ELISA kit. Collectively, the MAb 4D1-GNA sandwich ELISA is a promising technique for the rapid diagnosis of T. marneffei infection, which would facilitate the early treatment of patients with talaromycosis and it may be used to monitor treatment responses.